Waiting for the body to fail: limits to end-of-life communication in Canadian hospitals. (1st October 2016) - Nouvet, Elysée; Strachan, Patricia H.; Kryworuchko, Jennifer; Downar, James; You, John J.
Abstract: High-quality patient-centred care for hospitalised patients at the end of life requires health care teams to engage patients and families in communication and decision-making about goals of care. In the absence of such engagement, patient preferences may not be reflected in their care, and patients may be subjected to unwanted life-sustaining technologies such as mechanical ventilation and cardiopulmonary resuscitation. The DECIDE (DECIsion-making about goals of care for seriously ill, hospitalised medical patients) study was conducted with the aims of identifying barriers and ideas for improving end-of-life communication and decision-making with seriously ill patients in Canadian hospitals. Its qualitative component involved interviews with 30 physicians and nurses asking them to recall and describe hospital-based goals of care communication and decision-making incidents that had gone 'well' or 'unwell'. This article explores a dominant pattern in participants' accounts, which is a norm of waiting to initiate end-of-life discussions until seriously ill patients are within days or even hours of death. Attending to clinicians' explanations of when and why goals of care discussions are routinely delayed provides opportunity to clarify and critically consider important and normally unarticulated rationales underlying end-of-life discussion practices between health care teams and patients/families in Canadian hospitals.